STRATEGI GURU AGAMA HINDU DALAM MEMPERTAHANKAN MINAT BELAJAR EKSTRAKURIKULER TARI PADA SISWA - Elwis Nirmala Sari; Gede Eka Puja Dyatmika; Ni Putu Sasmika Dewi (Padma Sari: Jurnal Ilmu Pendidikan, 2021)
The purpose of this study was to give an describe about the strategies of Hindu religious teachers in maintaining interest in learning dance extracurriculars for students at Elementary School 117 Cendana Putih II. This study uses a descriptive qualitative approach. Data were collected by non-participant observation, free-guided interviews and documentation. Based on the results of the study, it was found that the dance extracurricular learning process took place in three processes, namely first, the initial process of preparing the sound system, saying prayers, recording the number of students present, then warming up; second, the core process, namely dividing groups into each student, then doing exercises in turns in each group; and third, the final process is saying the closing prayer, finally tidying up the sound system. The obstacles faced by teachers in maintaining interest in learning dance extracurricular are: first, the lack of facilities and infrastructure; secondly the lack of trainers; third, the lack of make-up personnel during performances; fourth, students who are difficult to manage (naughty); fifth, lack of mastery of some dances. In an effort to overcome the existing obstacles, the strategies used by teachers in maintaining interest in learning dance extracurriculars are: first, practicing in the school yard and asking parents for help in completing the performance clothes; second, asking for help from students in training; third, asking parents for help in preparing students' performances; fourth, changing the way of learning; and fifth, providing training guidance specifically to sixth grade Students.